2021
DOI: 10.1016/j.sdentj.2021.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of gastrointestinal diseases in the oral cavity

Abstract: Aim In this review, several gastrointestinal diseases that dentists may encounter in practice are highlighted and discussed. Materials and methods Using MEDLINE (PubMed), a comprehensive review of gastrointestinal diseases and their oral cavity manifestations was performed. Results Many gastrointestinal diseases present with oral symptoms that are detectable by dentists and dental hygienists. Often, oral manifestations of the disease may appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…In the current study, few participants reported a history of upper or lower gastrointestinal (GI) tract disease, with peptic ulcer, chronic gastritis, and inflammatory bowel disease being the most prevalent. Little is known about the prevalence of GI tract diseases in Saudi Arabia [ 18 ]. However, several studies have attempted to assess the prevalence of specific types of GI tract diseases, such as the study by Albaqawi et al, which found that the prevalence of peptic ulcer and duodenal ulcers among the general population in the Arar region of Saudi Arabia was 16.2% and 5.6%, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, few participants reported a history of upper or lower gastrointestinal (GI) tract disease, with peptic ulcer, chronic gastritis, and inflammatory bowel disease being the most prevalent. Little is known about the prevalence of GI tract diseases in Saudi Arabia [ 18 ]. However, several studies have attempted to assess the prevalence of specific types of GI tract diseases, such as the study by Albaqawi et al, which found that the prevalence of peptic ulcer and duodenal ulcers among the general population in the Arar region of Saudi Arabia was 16.2% and 5.6%, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the elevated bone fracture risk, osteoporosis, and osteopenia were studied and confirmed to be present in chronic inflammatory disorders, due to the action of inflammation factors (such as IL-6, TNF, and IL-1β) [ 24 ]. In addition, aspects such as poor nutrition, hemorrhage, or infection should be taken into consideration when assessing a dental implants survival rate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gingival tissues commonly have a pale pink color, although the color may be related to the person’s skin color, tissue thickness, degree of keratinization, and various comorbidities [ 33 , 42 ]. Additionally, the level of circulating hemoglobin may influence the coloration, and it should be noted that AD-related anemia is not uncommon due to a heterogeneous panel of digestive complications; some anemia-related oral anomalies are also detectable before the actual diagnosis of the underlying condition [ 43 , 44 ]. Dantas et al described the first case of oral multifocal melanoacanthoma (a rare, benign, pigmented lesion, usually involving both melanocytes and keratinocytes) in a 50-year-old patient who was newly diagnosed with synchronous AD and Basedow–Graves disease [ 31 ].…”
Section: Methodsmentioning
confidence: 99%